Sistem Endokrin: Sebuah Kajian Studi Literatur - Apriani Esma; Nurisma Mega Putri; Sinta Nabela; Ratih Pujiastuti; Yulianing Sukma; Miftakhul Janah; Liss Dyah Dewi Arini (Journal of Literature Review, 2025)
The endocrine system is a network of glands that produce and release hormones into the bloodstream to regulate various bodily functions. These hormones influence growth, metabolism, reproduction, mood, energy balance, and stress response. Each endocrine gland, such as the hypothalamus, pituitary, thyroid, parathyroid, pancreas, adrenals, ovaries, and testes, has its own function and produces different hormones. The endocrine system operates at a slower rate, but its effects are comprehensive and long-lasting, making it crucial for long-term physiological stability. Disruptions to this system can lead to serious illnesses requiring specialized medical treatment. This literature review synthesizes and contributes to the development of endocrinology and serves as a reference for medical practitioners, researchers, and students in understanding the complexity of the human body's hormonal regulatory system. This review uses a literature review method, with steps that include identifying, selecting, and synthesizing relevant research findings.